A Study On A Treatment System For Hyperhidrosis And A Solution That Combines Focused Ultrasound And Ultrasound Imaging Technology - et.al, Jong-Chul Park (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, for the treatment of axillary hyperhidrosis, we propose a driving algorithm for diagnosing the location / distribution / degree of sweat glands using ultrasound images and implementing a treatment device using high intensity focused ultrasound. Currently, treatment for axillary hyperhidrosis uses surgery to cut the skin itself or remove the sweat glands using an incision, but this has the disadvantage of scarring and long recovery time. To solve this, we propose a treatment device using high intensity focused ultrasound and a driving algorithm and a method for implementing a user interface environment.